Circulating levels and prognostic cut‐offs of sST2, hs‐cTnT, and NT‐proBNP in women vs. men with chronic heart failure. (5th May 2022) - Vergaro, Giuseppe; Gentile, Francesco; Aimo, Alberto; Januzzi, James L.; Richards, A. Mark; Lam, Carolyn S.P.; de Boer, Rudolf A.; Meems, Laura M.G.; Latini, Roberto; Staszewsky, Lidia; Anand, Inder S.; Cohn, Jay N.; et al.
Abstract: Aims: To define plasma concentrations, determinants, and optimal prognostic cut‐offs of soluble suppression of tumorigenesis‐2 (sST2), high‐sensitivity cardiac troponin T (hs‐cTnT), and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) in women and men with chronic heart failure (HF). Methods and results: Individual data of patients from the Biomarkers In Heart Failure Outpatient Study (BIOS) Consortium with sST2, hs‐cTnT, and NT‐proBNP measured were analysed. The primary endpoint was a composite of 1 year cardiovascular death and HF hospitalization. The secondary endpoints were 5 year cardiovascular and all‐cause death. The cohort included 4540 patients (age 67 ± 12 years, left ventricular ejection fraction 33 ± 13%, 1111 women, 25%). Women showed lower sST2 (24 vs. 27 ng/mL, P < 0.001) and hs‐cTnT level (15 vs. 20 ng/L, P < 0.001), and similar concentrations of NT‐proBNP (1540 vs. 1505 ng/L, P = 0.408). Although the three biomarkers were confirmed as independent predictors of outcome in both sexes, the optimal prognostic cut‐off was lower in women for sST2 (28 vs. 31 ng/mL) and hs‐cTnT (22 vs. 25 ng/L), while NT‐proBNP cut‐off was higher in women (2339 ng/L vs. 2145 ng/L). The use of sex‐specific cut‐offs improved risk prediction compared with the use of previously standardized prognostic cut‐offs and allowed to reclassify the risk of many patients, to a greater extent in women than men, and for hs‐cTnT than sST2 or NT‐proBNP. Specifically, up to 18% men and up to 57% women were reclassified, by using the sex‐specific cut‐off of hs‐cTnT for the endpoint of 5 year cardiovascular death. Conclusions: In patients with chronic HF, concentrations of sST2 and hs‐cTnT, but not of NT‐proBNP, are lower in women. Lower sST2 and hs‐cTnT and higher NT‐proBNP cut‐offs for risk stratification could be used in women.